EFFECT VARIATION OF TEMPERATURE AND STIRRING SPEED ON THE BENDING TEST OF FIBERGLASS FIBER COMPOSITE MATERIALS USING THE VACUUM ASSISTED RESIN INFUSION (VARI) METHOD - Setiawan, Ferry; Sakti , Faras Bimo; Wicaksono, Dhimas (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
This study aims to investigate the effect of temperature with constant agitation at 164 rpm on the fabrication of composite materials using the Vacuum Assisted Resin Infusion (VARI) method. In this research, composite materials were made with a polyester resin matrix reinforced with fiberglass. The challenge in the VARI process, which is the difficulty in controlling the viscosity of the solution when infused into the fibers, was addressed by using a stirrer in the feed resin tank. Heating was intended to increase the surface tension of the resin, allowing it to better penetrate the fibers. The variations used were stirring at a speed of 164 rpm and heating temperature variations of 28°C, 35°C, and 50°C. By stirring and heating the resin and catalyst solution, it is expected to achieve a more uniform viscosity, resulting in better composite material compared to methods without heating and without mixing. Based on the test results, the highest average bending strength was found in the specimen stirred with a mixer at 35°C, with a value of 359.91 MPa. The lowest average bending strength was found in the specimen with a temperature variation of 28°C, with a value of 133.7 MPa, and the bending strength at the temperature variation of 50°C was 348.81 MPa. The impact on bending strength is due to the presence of voids, which are gas or air trapped within the specimen structure. This is evidenced by micrographic analysis and density measurements, where the 28°C variation had the lowest density of 2.01 gr/cm3, while the 35°C and 50°C variations had the same density of 2.41 gr/cm3.